2010
DOI: 10.1007/s00056-010-1023-7
|View full text |Cite
|
Sign up to set email alerts
|

Precision of an Instrumentation-based Method of Analyzing Occlusion and its Resulting Distribution of Forces in the Dental Arch

Abstract: The measuring technique studied is superior to the usual methods, particularly with regard to force analysis per tooth. The level of accuracy is acceptable and no interference arising from change of foil or repeated measuring was detected. The method presented in this study therefore enhances routine diagnostics with marking foils. A combination of this method with marking foils would be ideal because the pressure-sensitive foils in this system do not produce any contact markings intraorally. This combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 12 publications
2
104
0
8
Order By: Relevance
“…Moreover, eight Occlusion Times were recorded for each subject, and a mean value was calculated in order to approach a representative OT value per subject. The accuracy of the T-Scan system recording has been shown to be not altered by repeated measures, which was confirmed by other sensor and system recording accuracy studies (Koos et al, 2010;Hirano et al, 2002). The T-Scan system has been shown to repetitively record timed occlusal contacts quantitatively and dynamically, during a continuous mandibular movement (Kerstein et al, 1997;Wang and Yin, 2012).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, eight Occlusion Times were recorded for each subject, and a mean value was calculated in order to approach a representative OT value per subject. The accuracy of the T-Scan system recording has been shown to be not altered by repeated measures, which was confirmed by other sensor and system recording accuracy studies (Koos et al, 2010;Hirano et al, 2002). The T-Scan system has been shown to repetitively record timed occlusal contacts quantitatively and dynamically, during a continuous mandibular movement (Kerstein et al, 1997;Wang and Yin, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…In 1987 Maness et al (1987) reported the development of the first computerized system designed for occlusal analysis (T-Scan I, Tekscan, Inc. Boston, MA, USA). Notwithstanding its early problems (Harvey et al, 1992), its hardware and software evolution over the past 30 years, and improvements made to this technology which are included in the T-Scan III version (T-Scan III, Tekscan Inc. Boston, MA, USA with T-Scan HD sensor), ensured it is precise and reliable (Koos et al, 2010;Hirano et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One might conclude that current belief systems surrounding paper mark interpretation have been a contributing factor in the widespread disagreement on occlusion. Alternatively, the T-Scan® system (T-Scan I-9; Tekscan, Inc. S. Boston, MA, USA) has demonstrated 95% force distribution reproducibility per subject from intercuspation to intercuspation [7]. The T-Scan® has a near-perfect linear correlation of 0.9995 when measuring and reporting on occlusal contact timing [8].…”
Section: Eugene or Usamentioning
confidence: 99%
“…A German research team validated the clinical use of the T-scan on 42 adult subjects 24 , estimating its error of measurement as 1%, its precision error as 2%, and its reliability error as 2.8%. They also asserted that changing the sensor or repeating the tests had no effect on the measurements obtained.…”
Section: --Scientific Validation Of the T Scan Systemmentioning
confidence: 99%